BENDING STRENGTH OF LIGNOCELLULOSIC MATERIALS IN SOFTENING CONDITION - Wahyu Dwianto; Ratih Damayanti; Teguh Darmawan; Prabu Satria Sejati; Fazhar Akbar; Danang Sudarwoko Adi; Adik Bahanawan; Yusup Amin; Dimas Triwibowo (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2020)
This research aimed to understand the softening behaviour and viscoelastic property of wood, rattan, and bamboo as lignocellulosic materials. Nine years-old fast growing teak wood [Tectona grandis L.f.], rattan [Calamus sp.], and 3 years-old andong bamboo [Gigantochloa pseudoarundinaceae (Steud.) Widjaja] were used for the experiments. The samples were taken from the bottom, middle and upper parts for wood and rattan, and that for bamboo were cut from the 1st to 20th internodes. Static bending tests were carried out in fresh (green) as control samples, air-dried, and softened by microwave heating (MW) for 1 min to determine modulus of rupture (MOR) and modulus of elasticity (MOE). The results showed that the MOR and MOE values of wood, rattan, and bamboo increased from fresh to air-dried condition, and decreased by MW. When compared at the same density, drastic increase was observed for the normalized MOR value in air-dried of rattan, i.e. 2.5 fold. However, the decreasing of all the normalized MOR values were almost the same, i.e. 0.5 fold when they were softened by MW. Remarkably increase was also appeared for the normalized MOE value in air-dried of rattan, i.e. 3.0 fold and decreased to almost zero by MW. These results indicated that rattan was more easily bent, followed by bamboo and then wood. Hydrothermal properties of chemical components significantly affected the changes of strength (MOR) and elastic properties (MOE). However, the differences in bending strength of wood, rattan, and bamboo were more likely due to differences in their anatomical structures.